6(3z+1)-z-22=

Simple and best practice solution for 6(3z+1)-z-22= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3z+1)-z-22= equation:


Simplifying
6(3z + 1) + -1z + -22 = 0

Reorder the terms:
6(1 + 3z) + -1z + -22 = 0
(1 * 6 + 3z * 6) + -1z + -22 = 0
(6 + 18z) + -1z + -22 = 0

Reorder the terms:
6 + -22 + 18z + -1z = 0

Combine like terms: 6 + -22 = -16
-16 + 18z + -1z = 0

Combine like terms: 18z + -1z = 17z
-16 + 17z = 0

Solving
-16 + 17z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + 17z = 0 + 16

Combine like terms: -16 + 16 = 0
0 + 17z = 0 + 16
17z = 0 + 16

Combine like terms: 0 + 16 = 16
17z = 16

Divide each side by '17'.
z = 0.9411764706

Simplifying
z = 0.9411764706

See similar equations:

| A+(a+1)=96 | | t^2+6t-35=0 | | ax-c=bx+5c | | -12-24d=3(a-15) | | 6x-25=x+34 | | 39=-2x+7x-1 | | 15x^2-17xy-4y^2=0 | | (m+7)*3=(m-3)*4 | | -16+a=-14 | | 3(z-1)-4(5-z)=2(6+z) | | 8x+2=7x(x-4)+5 | | 17+10x=2x+5-4x | | (m+7)*3=(m-3)*5 | | -2x^0= | | 1+4(3-5x)=4x+37 | | 7x=-41 | | -5x-7-x=-19 | | 4x/3-6=14 | | -6-7(k-6)=31-8k | | 4(3-2x)+4x=-4 | | 3(5x-6) | | 4y-4=y-16 | | 3t+1= | | C-7.88=9.25 | | -1+5(2n-2)=31+3n | | 3(2a+3)-4(3a-b)=15 | | 6(4x–3)–10x=14x-15 | | -158-7x=4x+51 | | 4(6n+9)-10= | | w2+36=12w | | 8(y-20=4Y | | 7+m=(m-3)+10 |

Equations solver categories